2018
DOI: 10.2355/isijinternational.isijint-2018-081
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Morphology of MnS Inclusions in Resulfurized Non-Quenched and Tempered Steel with Zr Addition

Abstract: Distribution and morphology of MnS inclusions in as-cast ingots and as-forged bars of two Zr-bearing resulfurized non-quenched and tempered (NQT) steels have been performed. In the low Zr-bearing steel (0.001 wt%), MnS inclusions, which are teardrop-shaped or rod-like in two-dimensional (2D) morphology and dendritic or skeletal in three-dimensional (3D) morphology, are mainly distributed and segregated at the grain boundaries. While in the high Zr-bearing steel (0.0066 wt%), MnS inclusions are spherical or ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…For example, IPFs only generate on the MnS + V(C, N) particles located inside of the prior austenite, if the MnS + V(C, N) particles are distributed along the boundary of the prior austenite, they would promote GBF formation instead. 16) Furthermore, in our previous study, 17) it was found that there was huge difference between two-dimensional (2D) and three-dimensional (3D) morphologies of type II MnS inclusions, as shown in Fig. 1.…”
Section: Effect Of Mns Inclusions Distribution On Intragranular Ferrimentioning
confidence: 82%
See 4 more Smart Citations
“…For example, IPFs only generate on the MnS + V(C, N) particles located inside of the prior austenite, if the MnS + V(C, N) particles are distributed along the boundary of the prior austenite, they would promote GBF formation instead. 16) Furthermore, in our previous study, 17) it was found that there was huge difference between two-dimensional (2D) and three-dimensional (3D) morphologies of type II MnS inclusions, as shown in Fig. 1.…”
Section: Effect Of Mns Inclusions Distribution On Intragranular Ferrimentioning
confidence: 82%
“…In the previous paper, 17) it was found the 3D morphologies of MnS inclusions were quite different in two sample steels. Most MnS inclusions in S1 are actually dendritic.…”
Section: Distributionmentioning
confidence: 85%
See 3 more Smart Citations